Pilocytic astrocytoma as a predominant component of a recurrent complex type DNT - Zakrzewski, Krzysztof; Biernat, Wojciech; Liberski, Pawel P.; Polis, Lech; Nowoslawska, Emilia (Folia Neuropathologica, 2009)
Dysembryoplastic neuroepithelial tumour (DNT) is a benign lesion of the cerebral hemispheres usually presenting minimal biological activity after surgical excision. We report an unusual case of a 7-year-old girl with a temporal lobe DNT, which recurred four years after subtotal resection of the tumour. In the recurrent lesion we identified pilocytic astrocytoma (PA) as a predominant component of the tumour. Small pieces of the removed tissues also disclosed remnants of DNT. Clinical presentation of the primary tumour consisted of partial simple seizures, while the recurrent tumour manifested with headache and vomiting. Likewise, the radiological appearance of both tumours was different. We conclude that patients with incompletely removed DNT may suffer local recurrence of that tumour. In rare cases development of a secondary, histologically different neoplasm may also occur.